Teacher Research: Learning to Listen - Jennifer Moore (Networks: An Online Journal for Teacher Research, 2002)
When friends from out of town visit, I often take them jogging around my hometown. I have routes I have run hundreds of times; they are so familiar, I run as if on automatic pilot. I seem to forget, though, that my guest has no idea that this is where I turn left, and that is the place where I cross the street to run on the other side. On more than one occasion, I have nudged a friend off the sidewalk or run right into them in my single-minded routine. I forget to ask questions, to explain, to direct, to instruct. I forget that my friends are not mind-readers, and that they may already have a route in mind. I forget that my running partner is peering around at unfamiliar sights, unaware of where we are heading and when we will finish. I forget to think outside of myself, and I have learned this year that I sometimes practice the same habits in my classroom.